2013
DOI: 10.1039/c3cc46117c
|View full text |Cite
|
Sign up to set email alerts
|

Light-controllable reflection wavelength of blue phase liquid crystals doped with azobenzene-dimers

Abstract: A new series of azobenzene-dimers were synthesized and doped into the blue phase liquid crystals to broaden the temperature range of BPs. It is found that not only can the reflection wavelength of BPI be reversibly controlled but BPI can also be transformed into the cholesteric phase owing to isomerization of azobenzene induced by light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…It has been experimentally and theoretically confirmed that the BP II and BP I exhibit simple cubic and body-centered cubic nanostructures (Figure 8(a)), respectively. Due to the unique 3D structures of BPLCs, they exhibit many revolutionary features such as optically isotropic and alignment-layer-free, while possess superior electrooptic properties and non-linear optical responses comparable to nematics [134][135][136][137][138][139][140][141][142][143][144][145][146][147][148]. Furthermore, because of the tightly wound spatial arrangement of the crystalline axis, the scattering loss due to thermal fluctuations of the director axis is considerably smaller than nematics, allowing longer interaction length and higher process efficiency.…”
Section: Fibre Arrays Filled With Blue Phase Liquid Crystalsmentioning
confidence: 98%
“…It has been experimentally and theoretically confirmed that the BP II and BP I exhibit simple cubic and body-centered cubic nanostructures (Figure 8(a)), respectively. Due to the unique 3D structures of BPLCs, they exhibit many revolutionary features such as optically isotropic and alignment-layer-free, while possess superior electrooptic properties and non-linear optical responses comparable to nematics [134][135][136][137][138][139][140][141][142][143][144][145][146][147][148]. Furthermore, because of the tightly wound spatial arrangement of the crystalline axis, the scattering loss due to thermal fluctuations of the director axis is considerably smaller than nematics, allowing longer interaction length and higher process efficiency.…”
Section: Fibre Arrays Filled With Blue Phase Liquid Crystalsmentioning
confidence: 98%
“…Sharing the similarity of using achiral azobenzene, Liu et al further confirmed the change of lattice spacing by Kössel diagrams [105]. So far, the largest tuning range in such systems, from red (*650 nm) to blue (*500 nm), was achieved by Chen et al using azobenzene dimers [106]. A fieldinduced transition from BPI to the cholesteric phase was also observed.…”
Section: Control Of Bp Photonic Bandgapmentioning
confidence: 67%
“…The periodic nanostructures are self-organized from the so-called double-twisted cylinders that are usually stabilized by the formation of defects or disclinations. As the 3D PCs, BPs feature remarkable bandgap tunability over an extensive spectrum in response to various external stimuli such as temperature [35,36], mechanical strength [37], electric field [38], and light [39][40][41]. The spectral band gap position of selective reflection can be readily predetermined by varying the chiral fraction of BP mixtures.…”
Section: Lc Blue Phasementioning
confidence: 99%